Photosynthetic characteristic and cold resistance of two-year old grafted tea plant in winter - LUO Yao-ping; WU shan; KANG Meng-li (浙江大学学报. 农业与生命科学版, 2002)
The photosynthetic characteristics were determined for the grafted tea plants with a variety of combinations of LongJing43/JiuKeng, ShuiXian/JiuKeng (scion/stock) and tea plants raised from seeds of the varieties LongJing43, ShuiXian and JiuKeng in the winter season; all of the plants had photosynthetic rate (Pn), dark respiration rate (Rd), stomatal conductance (Gs) and transpiration rate (Tr). They were at relatively low levels. Significant differences in Pn and Rd could be observed among different varieties and in a variety of combinations: the Pn of LongJing43 was the highest and the Pn of ShuiXian was the lowest. Compared with the non-grafted plants of the scion varieties, the values of Rd of the both grafted combinations LongJing43/JiuKeng, ShuiXian/JiuKeng were lower, but the values of Tr were higher and the values of Gs were slightly different. In the dark, almost no difference in Ci (intercellular CO2 concentration) was found among the grafted and non-grafted plants. In the sunlight, however, the values of Ci of the two grafted tea plants were higher than those of the non-grafted plants of their respective scion varieties. The Chlorophyll-A contents of grafted plants was the same for the scion variety obviously, was also higher than that of the non-grafted plant, and it was close that for the stock variety. But the Chlorophyll-B contents were nearly kept same in both the grafted and non-grafted plants. Under natural conditions in the field, the study of the cold resistance showed that the cold resistance of tea plants of both grafted and non-grafted were correlated very well with Pn.